STRATEGI ANGGOTA KOPERASI UNIT DESA (KUD) LEMBAH SAWIT DALAM MENINGKATKAN KESEJAHTERAAN (STUDI DESA SIALANG BARU KECAMATAN LUBUK DALAM KABUPATEN SIAK) - ", Supriyono; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of beehive New District of Lubuk In Siak. The purpose of this study is the first to find out what strategies Palm Valley KUD members to improve their welfare. The second objective is to determine the forms of service to every member of the Village Unit Cooperatives Palm Valley Village New beehive Analyzing the data in this study using Qualitative Research Methods. Qualitative Research Methods This is an analysis that seeks to provide a detailed picture of reality based on facts obtained from the field and also supported by the data in order to support the primary and secondary data exist. Qualitative research is presented in the form of words from the interview with the author of the respondents that describe the specific circumstances and understandable of Member Strategies Village Unit Cooperatives (KUD) Palm Valley In Improving Welfare. The results of field research shows that there is the occurrence of an unstable income or air fluctuates so that respondents feel lack in sufficient daily needs. Therefore, respondents need additional work or increase revenues by entrepreneurship, this method is more effective in improving the well-being because the respondents felt helped by their enterprises.Keywords: Member Cooperatives, Cooperative Village Unit, Welfare